The origin of the soft X-ray excess in the narrow-line Seyfert 1 galaxy SBS 1353 + 564. Issue 3 (10th August 2021) - Xu, Xinpeng; Ding, Nan; Gu, Qiusheng; Guo, Xiaotong; Contini, E
ABSTRACT: We present for the first time the timing and spectral analyses for a narrow-line Seyfert 1 galaxy, SBS 1353 + 564, using XMM-Newton and Swift multiband observations from 2007 to 2019. Our main results are as follows: (1) The temporal variability of SBS 1353+564 is random, while the hardness ratio is relatively constant over a time span of 13 yr; (2) We find a prominent soft X-ray excess feature below 2 keV that cannot be well described by a simple blackbody component; (3) After comparing the two most prevailing models for interpreting the origin of the soft X-ray excess, we find that the relativistically smeared reflection model is unable to fit the data above 5 keV well and the X-ray spectra do not show any reflection features, such as the Fe K α emission line. However, the warm corona model can obtain a good fitting result. For the warm corona model, we try to use three different sets of spin values to fit the data and derive different best-fitting parameter sets; (4) We compare the UV/optical spectral data with the extrapolated values of the warm corona model to determine which spin value is more appropriate for this source, and we find that the warm corona model with non-spin can sufficiently account for the soft X-ray excess in SBS 1353 + 564.